Developing and Implementing Corporate Governance Codes - World Bank (Washington, DC, 2012)
In recent years, voluntary codes have been increasingly employed across the globe to drive corporate governance reform. These guidelines, which emanate from stock exchanges, securities commissions, investors and investor associations, and supra-national organizations, set forth "best practice" recommendations across a range of topics that listed companies, shareholders, and other relevant parties are encouraged but not obliged to follow. Today, corporate governance codes are found in over 70 countries. It is relatively straightforward to develop corporate governance codes. The challenge lies in ensuring their effective implementation and enforcement, as evidenced by the complaints heard in some countries that governance codes have not lived up to their promise to spur enduring improvements in corporate practices. The concerns voiced range from poorly written guidelines to inadequate levels of compliance by companies to "box-ticking" by investors. This opinion piece will begin with an examination of the principal uses and key design characteristics of a corporate governance code.